Trouble in paradise: resilience and Vancouver's second life in the "new economy". Issue 2 (17th February 2016) - Siemiatycki, Elliot; Hutton, Thomas; Barnes, Trevor
Abstract : Resilience is an increasingly important concept within urban studies, economic geography, and evolutionary economics for measuring the capacity of city-regions to respond to economic shocks. In this article, we provide a sympathetic critique of the resilience metaphor in urban studies, which we explicate through an analysis of the recent history of the Vancouver economy. On the surface, Vancouver seemingly showed resilience when it overcame the abrupt decline of its resource-based economy in the 1980s, and established an alternative flourishing "new economy" by the 1990s. But over the last five years, the key local "creative" industries such as video game development and film production have suffered, with a number of large firms leaving Vancouver, and industry employment declining sharply. Drawing on more than 40 interviews conducted over a five-year period with members of the local video game community, our paper documents the rise and more recent decline of Vancouver's "new economy" sector. Our research raises questions about the value of the resilience metaphor in urban studies and highlights the difficulties facing city-regions reliant on highly mobile "new economy" industries.